2020
DOI: 10.21203/rs.3.rs-32375/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Knowledge, attitude and practice of the Sudanese people towards COVID-19: An online survey

Abstract: Background: The Novel Corona Virus (SARS-CoV-2) had emerged to affect the human population in 2019 causing COVID-19 pandemic. The only preventive measures available are social distancing, hand washing and face masks. This study aims to assess the knowledge, attitude and practice of the Sudanese people towards COVID-19.Methods: An online cross-sectional study targeting adult Sudanese people was conducted in April 2020. The study used a self-administered questionnaire containing 18 knowledge questions, 5 questi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 7 publications
3
14
1
1
Order By: Relevance
“…Moreover, participants who were unable to read and write were 1.6 times more likely to have inadequate knowledge of COVID-19 compared with those who had attended tertiary-level education. This finding is similar to studies conducted in Syria, 22 Iran, 23 rural areas in China, 33 Sudan, 29 Bangladesh 30 and Nepal. 34 In Ethiopia, most of the unable-to-read-and-write segment of the population is found in rural areas.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Moreover, participants who were unable to read and write were 1.6 times more likely to have inadequate knowledge of COVID-19 compared with those who had attended tertiary-level education. This finding is similar to studies conducted in Syria, 22 Iran, 23 rural areas in China, 33 Sudan, 29 Bangladesh 30 and Nepal. 34 In Ethiopia, most of the unable-to-read-and-write segment of the population is found in rural areas.…”
Section: Discussionsupporting
confidence: 90%
“…This finding showed that the proportion of inadequate knowledge about COVID-19 prevention was 54.11% (95% CI 50.6% to 57.6%), which is higher than studies conducted in Debre Birhan University, Ethiopia (26.2%), 21 Syria (40%), 22 Iran (39.2%), 23 Bangladesh (51.7%), 24 Saudi Arabia (18.4%), 25 across the world (20.1%), 26 Malaysia (19.5%), 27 India (13.3%), 28 three Middle Eastern countries (Jordan, Saudi Arabia and Kuwait) (33.9%) 11 and Sudan (9.4%). 29 The differences in the level of knowledge have been subjected to variations in the cut-off values. In addition, the discrepancies might be due to differences in community awareness creation through mass media and social media.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…After title and abstract screening, 99 papers were retrieved for full paper review. After the full paper screening, 33 studies met our full review inclusion criteria [ 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 ]. As reported in Figure 1 , the first screen based on the inclusion criteria saw a large number of publications not being included.…”
Section: Resultsmentioning
confidence: 99%